A golden access to acenopentalenes - Wurm, Thomas; Rüdiger, Elias; Schulmeister, Jürgen; Koser, Silke; Rudolph, Matthias; Rominger, Frank; Bunz, Uwe H. F.; Hashmi, A. Stephen K. (Chemistry - a European journal, 2018)
By employing gold catalysis, starting from dialkynylated acenes a series of novel un-symmetrical aceno-annulated dibenzopentalenes has been prepared. The achieved yields range from 62-68 %. The fused systems contain naphthalene, anthracene, tetracene, and pentacene units. All new compounds are soluble and stable under standard conditions. The optical properties of the systems are dominated by the dibenzopentalene core for the smaller representatives, while for the anthracene-pentacene-based aceno-benzopentalenes the optical properties of the acene group dominates. Preliminary morphology tests on thin films showed a reverse trend between crystal size and molecule size.
First published: 22 December 2017
Gesehen am 28.06.2018